EFFECT OF QUESTION CARD LEARNING MEDIA OF NHT TYPE COOPERATIVE LEARNING MODEL ON LEARNING OUTCOMES IN ACID-BASE CONCEPTS AMONG STUDENT OF MIPA, MAKASSAR CITY - Munawwara, Munawwara; Salempa, Pince; Allo, Eda Lolo (UNESA Journal of Chemical Education, 2023)
This quasi-experimental study seeks to ascertain the effect of Question Card learning media on the Numbered Head Together (NHT) type Cooperative learning model toward learning Outcomes of Class XI MIPA Students on the subject matter of acids and bases. The research design used was a posttest-only control design. The sampling technique was carried out by simple random sampling, so that 2 sample classes were obtained as the experimental and control class. The instrument used in this study was the learning achievement test. The learning outcomes data obtained were analyzed using descriptive and inferential statistical analysis. The results of the descriptive analysis showed that the average experimental class learning result was 77.97 higher than the control class learning average 69.76. The results of the normality test indicated that the experimental class data were normally distributed while the control class data were not normally distributed and the results of the homogeneity test indicated that both classes came from homogeneous populations. Therefore, the hypothesis test used is a non-parametric test, the results of the Mann-Whitney test reveal that Zcount (2.36) > Ztable (1.65). There is an effect of the Question Card learning media on the NHT type Cooperative learning model on the learning outcomes on the subject matter of Acids and Bases.